Mummies : the newest, coolest, and creepiest - Tanaka, Shelley (Harry N. Abrams, 2005)
Examines mummy discoveries made around the world, and looks at how advances in forensic science and other investigative techniques are helping scientists learn about the lives and deaths of these sometimes ancient, preserved bodies.